Ecclesiastes/Song of Songs - Provan, Iain William (Grand Rapids, MI Zondervan, 2001)
Includes bibliographical references and indexes.
Keywords: Bible. O.T. Ecclesiastes -- commentaries; Bible. O.T. Song of Solomon -- commentaries